Factors associated with shared decision making among primary care physicians: Findings from a multicentre cross‐sectional study. (2nd August 2017) - Menear, Matthew; Garvelink, Mirjam Marjolein; Adekpedjou, Rhéda; Perez, Maria Margarita Becerra; Robitaille, Hubert; Turcotte, Stéphane; Légaré, France
Abstract: Background: Despite growing recognition that shared decision making (SDM) is central for patient‐centred primary care, adoption by physicians remains limited in routine practice. Objective: To examine the characteristics of physicians, patients and consultations associated with primary care physicians' SDM behaviours during routine care. Methods: A multicentre cross‐sectional survey study was conducted with 114 unique patient‐physician dyads recruited from 17 primary care clinics in Quebec and Ontario, Canada. Physicians' SDM behaviours were assessed with the 12‐item OPTION scale scored by third observers using audio‐recordings of consultations. Independent variables included 21 physician, patient and consultation characteristics. We assessed factors associated with OPTION scores using multivariate linear regression models. Results: On the OPTION scale, where higher scores indicated greater SDM behaviours, physicians earned an overall mean score of 25.7±9.8 of 100. In the final adjusted regression model, higher OPTION scores were associated with physicians' social participation (involvement in one committee β=5.75, P =.04; involvement in two or more committees β=7.74, P =.01), patients' status as employed (β=6.48, P =.02), clinically significant decisional conflict in patients (β=7.15, P =.002) and a longer duration of consultations (β=0.23, P =.002). Conclusion: Physicians' social participation, patients' employment status and decisional conflict and the duration of consultations were associated with primary care physicians' SDM behaviours in routine care. These factors should be considered when designing strategies to implement SDM and promote more patient‐centred care in primary care.